Weaving and binding immigrant gods and female immortals in ancient Japan - Como, Michael (Honolulu : University of Hawaii Press, 2010)
"Among the most exciting developments in the study of Japanese religion over the past two decades has been the discovery of tens of thousands of ritual vessels, implements, and scapegoat dolls (hitogata) from the Nara (710-784) and early Heian (794-1185) periods. Because inscriptions on many of the items are clearly derived from Chinese rites of spirit pacification, it is now evident that previous scholarship has mischaracterized the role of Buddhism in early Japanese religion. Weaving and Binding makes a compelling argument that both the Japanese royal system and the Japanese Buddhist tradition owe much to continental rituals centered on the manipulation of yin and yang, animal sacrifice, and spirit quelling. Building on these recent archaeological discoveries, Michael Como charts an epochal transformation in the religious culture of the Japanese islands, tracing the transmission and development of fundamental paradigms of religious practice to immigrant lineages and deities from the Korean peninsula."--BOOK JACKET.
Immigrant gods on the road to Jindo -- Karakami and animal sacrifice -- Female rulers and female immortals -- The queen mother of the west and the ghosts of the Buddhist tradition -- Shamanesses, lavatories, and the magic of silk -- Silkworms and consorts -- Silkworm cults in the heavenly grotto : Amaterasu and the children of Ama No -- Hoakari.
Includes bibliographical references (p. 279-294) and index.
Description based on print version record.
Keywords: Japan -- Religion; Electronic books